Giant lipoma of descending colon masquerading as a colonic malignancy. Issue 2 (4th February 2021) - Vishwajeet, Vikarn; Soni, Subhash; Elhence, Poonam; Khera, Sudeep
Abstract : Lipomas of the large intestine are uncommon tumour. They are often innocuous and do not cause any clinical problem, particularly if they are small (<2 cm) is size. However, they can give rise to significant clinical symptoms if they become large and can be mistaken for colorectal carcinoma. Herein, a giant submucosal lipoma of descending colon is described, which was preoperatively suspected of carcinoma and underwent left hemicolectomy. The diagnosis was only reached after pathological examination of the resected tumour. The case highlights that a large colonic lipoma still poses diagnostic difficulty. Accurate diagnosis of the lipomas is important as they can be removed by endoscopic polypectomy or segmental resection, obviating the need of unnecessary major surgical resection.